Glucokinase is required for high‐starch diet‐induced β‐cell mass expansion in mice. Issue 9 (30th March 2021) - Tsuchida, Kazuhisa; Nakamura, Akinobu; Miyoshi, Hideaki; Yang, Kelaier; Yamauchi, Yuki; Kawata, Shinichiro; Omori, Kazuno; Takahashi, Kiyohiko; Kitao, Naoyuki; Nomoto, Hiroshi; Kameda, Hiraku; Cho, Kyu Yong; et al.
Abstract: Aims/Introduction: We aimed to determine whether glucokinase is required for β‐cell mass expansion induced by high‐starch diet (HSTD)‐feeding, as has been shown in its high‐fat diet‐induced expansion. Materials and Methods: Eight‐week‐old male wild‐type ( Gck +/+ ) or glucokinase haploinsufficient ( Gck +/− ) mice were fed either a normal chow (NC) or an HSTD for 15 weeks. The bodyweight, glucose tolerance, insulin sensitivity, insulin secretion and β‐cell mass were assessed. Results: Both HSTD‐fed Gck +/+ and Gck +/− mice had significantly higher bodyweight than NC‐fed mice. Insulin and oral glucose tolerance tests revealed that HSTD feeding did not affect insulin sensitivity nor glucose tolerance in either the Gck +/+ or Gck +/− mice. However, during the oral glucose tolerance test, the 15‐min plasma insulin concentration after glucose loading was significantly higher in the HSTD group than that in the NC group for Gck +/+, but not for Gck +/− mice. β‐Cell mass was significantly larger in HSTD‐fed Gck +/+ mice than that in NC‐fed Gck +/+ mice. In contrast, the β‐cell mass of the HSTD‐fed Gck +/− mice was not different from that of the NC‐fed Gck +/− mice. Conclusions: The results showed that HSTD feeding would increase pancreatic β‐cell mass and insulin secretion in Gck +/+, but not Gck +/− mice. This observation implies that glucokinase in β‐cells would be required for the increase in β‐cell mass induced by HSTD feeding. Abstract : Our results indicated that high‐starch diet feeding augmented insulin secretion and increased pancreatic beta‐cell mass in wild‐type mice, but not in the beta cell‐specific glucokinase haploinsufficient mice. These findings demonstrated that glucokinase in beta cells is required for increasing beta cell mass induced by high‐starch diet feeding.